Clive Cussler The sea wolves [large type] - Cussler, Clive; Du Brul, Jack B. (Cussler, Clive. Isaac Bell novels, 2022)
"In the summer of 1914, Detective Isaac Bell is asked to investigate a cache of missing rifles but discovers something much more sinister. Whoever broke into this Winchester factory wasn't looking to take weapons; they wanted to leave a radio transmitter, set to summon a fleet of dreaded German U-boats. Someone is trying to keep American supplies from reaching British shores. Bell must hunt down a new piece of technology that is allowing the Germans to rule the seas from New York to England. With the outcome of the war at stake and Franklin Roosevelt's orders on the line, Bell will risk everything to stop the U-boats before they strike again"--